Morphological Diversity of Endophytic Bacteria Peppermint (Mentha Piperita L.) - Rangga Ardiansyah; Sartika Wati Dwi Sapitri; Muhammad Naufal Dzakwan; Nisa Muhammad Thalib; Monika Thamara; Lia Putri Maharani; Risky Hadi Wibowo; Sipriyadi Sipriyadi; Welly Darwis (Universitas Labuhanbatu, 2025)
Background: The peppermint plant (Mentha piperita L.) is a type of medicinal plant that is widely found in temperate regions, especially Europe, North America and Africa. This plant contains essential oils, menthol, and menthone, menthafuran, sesquiterpenes, triterpenes, flavonoids, carotenoids, tannins and various minerals are also widely contained in peppermint leaf oil (M. piperita L.). The purpose of this study was to isolate and determine the morphological diversity of endophytic bacteria from peppermint plants (M. piperita L.). Methodology: The method used in this study is to take isolation samples, pure culture, characterization and gram staining to determine whether it includes gram-negative or positive bacteria. The results of the study of 12 cultures of endophytic bacterial isolates from plants (M. piperita L.) were taken 10 isolates from each different culture media. Findings: The results of morphological observations of bacterial colonies show diverse characteristics in terms of surface, appearan, ceelevation, edges, and colour. Gram Staining Test of Endophytic Bacterial Isolates from the roots, leaves, and stems of mint plants against endophytic bacteria showed that there were gram-positive and gram-negative bacterial isolates. Then the results of bacterial cell shape morphology have a diversity of Cocobacil, Coccus, and Bacil forms so it can be concluded that endophytic bacterial isolates from peppermint plants (M. piperita L.) have varied morphological diversity. Contribution: Data on the morphological diversity of endophytic bacteria from M. piperita L. provides important basic data for further research on the potential of M. piperita L. endophytic bacteria